Evaluation of indigenous methanotroph isolates on greenhouse gases mitigation in lowland rice fields of Cauvery Delta Zone, Tamil Nadu - Bharathi, M Jeya; Bharani, A; Rajappan, K; Vanitha, K (ORYZA-An International Journal of Rice, 2018)
Global warming is a serious problem caused by the greenhouse gases. Though methane emission from rice fields is also responsible for the earth warming, its cultivation cannot be prohibited since rice is a major food crop for Asian countries. Methanogens are anaerobic organisms that produces methane, whereas, methanotrophs are microaerophilic organism that uses methane as a carbon source.Hence,a liquid microbial consortium was developed using two indigenous methanotroph isolates from Keelamaruthuvakudi and Aduthurai. A field experiment was conducted to study the effect of liquid microbial consortium on greenhouse gases mitigation in low land rice (ADT 49) fields. The results indicated that application of 75% recommended dose of NPK fertilizers +azophos (2 kg/ha)+methanotrophs (500 ml/ha)reduced the greenhouse gases emission @ methane (4.00 mg/ m2/h), N2O (9.86μ mol/ m2/s) and CO2 (0.066μg N/m2/h) when compared to methanotroph uninoculated control.